Beyond Connectivity: A Strategic Management Framework for Sustainable Digital Education Ecosystems in Remote Areas - Muslimin, Muslimin; Dwiyanti, Andi Amitya Resty; Misnawati, Misnawati; Yusriadi, Yusriadi; Ismail, Ismail (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2026)
This study aims to identify essential elements and strategies needed to build an inclusive and sustainable digital education ecosystem in remote areas of Indonesia. The research used a qualitative case study design. Data were collected through in-depth interviews and participant observation with 15 key stakeholders. The findings indicate a hierarchical dependency, where the instability of physical infrastructure—particularly connectivity, devices, and electricity—creates a scarcity model that hinders sustainable digital adoption. This situation creates a functional competency gap: teachers are pedagogically ready but hampered by low technical confidence. To overcome these obstacles, stakeholders implemented bricolage adaptation strategies, such as separating the learning process from real-time internet dependence through offline methods and utilizing collective community funding. The study also found that socio-cultural anchoring—through the integration of local wisdom in digital content and active community participation—serves as a crucial “soft infrastructure” in ensuring program sustainability. In contrast to previous techno-centric studies, this research formulates a Locally-Based Digital Ecosystem Model that shows that the sustainability of digital education in 3T areas depends not only on access to technology but also on the integration of technical adaptation and cultural resilience.